Il Trovatore = The Troubadour - Fisher, Burton D. (Opera Journeys, 2000)
A comprehensive opera-guide, featuring Principal Characters in the Opera, Brief Story Synopsis, Story Narrative with Music Highlight Examples, and Burton D. Fisher's insightful and in depth Commentary and Analysis.
"Italian opera in four acts, music by Giuseppe Verdi ; libretto by Salvatore Cammarano, after El Trovador (1836), a tragedy by the Spanish playwright, Antonio García Gutiérrez (The final libretto was completed by Emmanuele Bardareafter Cammarano's premature death)."
Keywords: Verdi, Giuseppe, -- 1813-1901. -- Trovatore.; Verdi, Giuseppe, -- 1813-1901. -- Trovatore -- Criticism and interpretation.; Trovatore (Verdi, Giuseppe); Operas -- Stories, plots, etc.; MUSIC -- Genres & Styles -- Opera.; Operas; Criticism, interpretation, etc.; Stories, plots, etc.